Differences in Perception of Musical Stimuli among Acoustic, Electric, and Combined Modality Listeners. - Prentiss, Sandra M.; Friedland, David R.; Nash, John J.; Runge, Christina L. (Journal of the American Academy of Audiology, 2015)
Background: Cochlear implants have shown vast improvements in speech understanding for those with severe to profound hearing loss; however, music perception remains a challenge for electric hearing. It is unclear whether the difficulties arise from limitations of sound processing, the nature of a damaged auditory system, or a combination of both. Purpose: To examine music perception performance with different acoustic and electric hearing configurations. Research Design: Chord discrimination and timbre perception were tested in subjects representing four daily-use listening configurations: unilateral cochlear implant (Cl), contralateral bimodal (ClHA), bilateral hearing aid (HAHA) and normal-hearing (NH) listeners. A same-different task was used for discrimination of two chords played on piano. Timbre perception was assessed using a 10-instrument forced-choice identification task. Study Sample: Fourteen adults were included in each group, none of whom were professional musicians. Data Collection and Analysis: The number of correct responses was divided by the total number of presentations to calculate scores in percent correct. Data analyses were performed with Kruskal-Wallis one-way analysis of variance and linear regression. Results: Chord discrimination showed a narrow range of performance across groups, with mean scores ranging between 72.5% (CI) and 88.9% (NH). Significant differences were seen between the NH and all hearing-impaired groups. Both the HAHA and CIHA groups performed significantly better than the CI groups, and no significant differences were observed between the HAHA and CIHA groups. Timbre perception was significantly poorer for the hearing-impaired groups (mean scores ranged from 50.3-73.9%) compared to NH (95.2%). Significantly better performance was observed in the HAHA group as compared to both groups with electric hearing (CI and CIHA). There was no significant difference in performance between the CIHA and Cl groups. Timbre perception was a significantly more difficult task than chord discrimination for both the Cl and CIHA groups, yet the easier task for the NH group. A significant difference between the two tasks was not seen in the HAHA group. Conclusion: Having impaired hearing decreases performance compared to NH across both chord discrimination and timbre perception tasks. For chord discrimination, having acoustic hearing improved performance compared to electric hearing only. Timbre perception distinguished those with acoustic hearing from those with electric hearing. Those with bilateral acoustic hearing, even if damaged, performed significantly better on this task than those requiring electrical stimulation, which may indicate that CI sound processing fails to capture and deliver the necessary acoustic cues for timbre perception. Further analysis of timbre characteristics in electric hearing may contribute to advancements in programming strategies to obtain optimal hearing outcomes.